Engineering Waste Management Systems: Efficiency Through Strategic Planning and Management Tools - Ugli, Isroilov Sardorbek Solijon; Ghate, Atul Dattatraya (International Journal of Engineering, Science and Information Technology, 2025)
Expanded life expectancy and higher health consciousness have been the pivotal contributors to the growth of the medical service sector. With a growing population, medical service facilities have additionally increased largely and proportionately the quantity of BMW produced. The growing quantity of biomedical waste is a public health issue internationally, drawing concern from all health authorities, associations and the government. The current biomedical waste management system in India has flaws that lead to inefficient and unproductive biomedical waste treatment procedures.  A thorough understanding of the types and quantities of waste that must be managed is necessary for the first crucial stage in the biomedical waste management system, which is creating a trustworthy waste management plan.  Therefore, the current study considered both identifying constraints related to biomedical waste management in hospitals and situational evaluation of biomedical waste management techniques.  By using interpretive structural modelling and environmental auditing techniques, this study seeks to assess current biomedical waste management procedures and investigate several obstacles that stand in the way of an efficient and successful biomedical waste management system.